Reciprocity and honesty in capital budgeting: Positive spill-over effects of reporting - Andreas Ostermaier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Capital rationing and reporting are often combined to allocate resources in firms. Trust in managers' honest reports and distrustful control create an interesting tension. How do managers respond to this ambivalence of trust and control? We develop an analytical model to predict, first, that managers reciprocate distrust; they misreport heavily so as to sabotage profitable investments. Second, reporting reduces in turn sabotage because managers are reluctant to lie. Third, honesty spills over, in addition, to inhibit managers' reciprocity. Evidence from a laboratory experiment supports our predictions. Our study ties capital rationing and reporting to the psychological factors of reciprocity and honesty and helps us understand their effects in budgeting. From a managerial viewpoint, the value of reporting, even in combination with capital rationing, may be as interesting to see as how sabotage further exacerbates the underinvestment which is known to arise from capital rationing.
Keywords: D03; G31; M41; 330